Pattern of blood component cross-matching and their utilization in a tertiary care hospital of Jammu region - Yasmeen, Irm; Ahmed, Ibrar; Sidhu, Meena (International Journal of Research in Medical Sciences, 2018)
Background: Transfusion of donated blood remains the mainstay of treatment for a wide range of medical and surgical conditions. Although it can save life, but transfusion of blood is not without risk. Clinicians should cautiously assess the appropriateness of indications before requesting various blood components thereby preventing misuse of blood and unnecessary exposure of patient to various transfusion transmitted infections and antibodies production. This study was conducted to determine the pattern of whole blood (WB) and blood component cross-matching and their utilization and to minimize the inappropriate use of blood and its components. Methods: This cross-sectional prospective study was performed at SMGS Hospital Blood Bank, Jammu from April 2016 to September 2016. The requisition forms were analysed at the reception counter and inside the pre-transfusion testing laboratory for any error. The department wise utilization of blood and its components, Crossmatching to transfusion (C/T) ratio, transfusion probability (T%) and transfusion index (TI) were calculated. Results: A total of 14376 requests for cross-matching of blood and its components were received. All the units were cross-matched. Out of these, 12766(88.8%) units of blood and its components were issued to various departments. The most common indication for using packed red cells and whole blood was anemia and bleeding (APH/PPH/Trauma). The total C/T Ratio, transfusion probability (T%) and Transfusion index(TI) of various blood components were 1.12:1, 88.8% and 0.88 respectively. Conclusions: Our study indicates efficient usage of blood and its component. However, awareness is still needed amongst the clinicians and residents to ensure the appropriate use of blood and its components in the future as well. Hospital transfusion committee has to develop transfusion guidelines and subsequent implementation of such guidelines to assure effective blood utilization. MSBOS (maximum surgical blood ordering schedule) should be formulated for elective procedures with regular auditing, feedback, and modifications to improve blood ordering and utilization.